Evaluation of electrodiagnostic changes in patient with Multiple Sclerosis - Samaheh Raftari; Morteza Saeedi (Reviews in Clinical Medicine, 2014)
Although demyelination along the axons is the main manifestation of Multiple sclerosis (MS), peripheral nervous system (PNS) could be affected potentially too. In some studies PNS involvement is estimated to be more than 50 percent in MS patients. Accordingly, objective tests to confirm the severity of PNS involvement might be crucial in patients` management. Modern technological advances lead to innovation of computerized electrodiagnostic (EDX) techniques in recent years. Nerve conduction studies (NCS) provide reliable data about neuropathies. Although the frequency of PNS involvement varies in different population of MS patients, recognizing clinical and subclinical PNS impairments in MS patients is important for the treatment.